Nonlinear Image Blending for Dual-Energy MDCT of the Abdomen: Can Image Quality Be Preserved If the Contrast Medium Dose Is Reduced? - Mileto, Achille (2014)
OBJECTIVE. The objective of this study was to compare the image quality of a dual- energy nonlinear image blending technique at reduced load of contrast medium with a simulated 120-kVp linear blending technique at a full dose during portal venous phase MDCT of the abdomen. SUBJECTS AND METHODS. Forty-five patients (25 men, 20 women; mean age, 65.6 ± 9.7 [SD] years; mean body weight, 74.9 ± 12.4 kg) underwent contrast-enhanced single-phase dual-energy CT of the abdomen by a random assignment to one of three different contrast medium (iomeprol 400) dose injection protocols: 1.3, 1.0, or 0.65 mL/kg of body weight. The contrast-to-noise ratio (CNR) and noise at the portal vein, liver, aorta, and kidney were compared among the different datasets using the ANOVA. Three readers qualitatively assessed all datasets in a blinded and independent fashion. RESULTS. Nonlinear blended images at a 25% reduced dose allowed a significant improvement in CNR (p < 0.05 for all comparisons), compared with simulated 120-kVp linear blended images at a full dose. No statistically significant difference existed in CNR and noise between the nonlinear blended images at a 50% reduced dose and the simulated 120-kVp linear blended images at a full dose. Nonlinear blended images at a 50% reduced dose were considered in all cases to have acceptable image quality. CONCLUSION. The dual-energy nonlinear image blending technique allows reducing the dose of contrast medium up to 50% during portal venous phase imaging of the abdomen while preserving image quality.